PEMANFAATAN DATA PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS (SIG) UNTUK ANALISA BANJIR (STUDI KASUS: KECAMATAN WANAREJA KABUPATEN CILACAP) - Muhammad Zaki Zamani; Septiani Ari Dwijayanti; Pipit Wijayanti (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2023)
Wanareja Subdistrict is one of 24 subdistricts in Cilacap Regency which experiences floods every year. In 2022, until September, Wanareja District will experience four floods. Utilization of remote sensing and Geographic Information Systems (GIS) can be used to determine the level of vulnerability to flood disasters. This study aims to process the parameters that cause flooding and create a flood hazard map using Geographic Information System (GIS) aplikasi. The method used is scoring, weighting, and overlaying the parameters that cause flooding, namely land use, rainfall, slope, altitude, soil type, and river buffer which are processed using the ArcGIS 10.8 application. The results of this study are in the form of a flood vulnerability map which shows that Wanareja District has three levels of flood vulnerability, namely safe, low, and moderate. The low vulnerability level is the area that has the largest area, namely 9927.26 Ha (52%), while the medium vulnerability level is 7254.53 Ha (38%), and the safe vulnerability level has the smallest area, namely 1909.09 Ha (10%) of the total area in the Wanareja District of 19090.88 Ha